P144 Why can specific challenges be negative in workers with good evidence of occupational asthma?. (December 2018) - Moore, VC; Robertson, AS; Walters, GI; Burge, PS
Abstract : Background: Specific challenge tests (SIC) are regarded as the reference standard in the diagnosis of occupational asthma. As part of an audit of specific inhalation testing 2006–2015 we have identified 12 workers whose SIC were negative but for which there was strong alternative evidence of occupational asthma. We have looked for causes for the discordance. Methods: We performed SIC in 125/343 workers with possible occupational asthma with latency referred to us from 2006–2015. In 72 the SIC was negative, 12 of these had serial PEF evidence of occupational asthma with positive scores from the Oasys computer assisted diagnostic program both for the Area-Between Curves (ABC)>15 litres/min/hour and discriminant analysis (Oasys score)>2.5 (combined specificity 100%, sensitivity 60% with positive SIC as positive referent and non-exposed asthmatics as negative referent), and both scores becoming negative after relocation with the same employer. It is likely that at least these 12 had falsely negative SICs. We have investigated why the SICs may have been negative following a subjective review of all data. Results: The mean ABC score was 30.3 l/min/hour (range 60.8–19.1) pre-relocation and −12.1 l/min/hour (range −48.6 -+9.9) post-relocation. The Oasys discriminant scores were 3.52 (4–2.67) pre-relocation and 1.73 (2.29–1.13) post-relocation. The cause was likely to be an agent not tested in SIC despite testing 4–8 agents each in 7 workers. Likely missed causes included a mouldy school building (figure 1), environmental welding fume, cleaning materials and a lack of protein source for chlorine-releasing agents. In 2 there was no exposure to the likely cause for >6 months, in 3 the control days were too unstable to identify late reactions, perhaps related to LABA withdrawal pre-challenge, and in 3 the work-exposures were likely to be much higher than used in the SIC (MDI, shrink-wrap and plastic moulding) (>1 reason possible). 9 were taking ICS during SIC which may have limited reactions. Conclusion: Occupational asthma is still possible despite negative SIC. The figure shows the mean hourly PEF on days at home and days at work in a DT technician before (top) and after (bottom) relocating to new buildings with the same work exposures.